Computers in Cardiology, 2003 2003
DOI: 10.1109/cic.2003.1291254
|View full text |Cite
|
Sign up to set email alerts
|

Some considerations on the IPFM model for the heart rate variability analysis

Abstract: The IntroductionIt is commonly admitted that the IPFM model is a possible model for the generation of the R waves time occurrences. The use of the outputs ¢ ¥ £ s for the frequency analysis of the heart rate variability has been studied in detail in several papers. The latest [1], [2] gives some recommendation in using these outputs in order to reduce or cancel the distortion of the spectrum. The problem of the choice for the model input is not usually addressed and is simplified using a single or a sum of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…To do so, a model linking the HP and the respiratory function was introduced. In a previous study (24), we demonstrated that the pulse frequency modulation (PFM) model was a candidate for this aim. In the following, the PFM results are given under stationary conditions.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…To do so, a model linking the HP and the respiratory function was introduced. In a previous study (24), we demonstrated that the pulse frequency modulation (PFM) model was a candidate for this aim. In the following, the PFM results are given under stationary conditions.…”
Section: Experimental Designmentioning
confidence: 99%
“…Moreover, it has been demonstrated (25) that the following expressions, where the index k has been omitted, are valid in nonstationary conditions. Considering the PFM model (24), the time of occurrence t k was the solution of the equation:…”
Section: Experimental Designmentioning
confidence: 99%
“…El modelo genera un latido integrando una señal de entrada hasta que alcanza un umbral preestablecido. En ese instante se produce un pulso y el integrador se reinicia (17). El segundo componente es la contribución generada por los sistemas simpático y parasimpático producto de las mediciones y variaciones de la PA y por último la contribución de los receptores ubicados en la aurícula derecha y las arterias pulmonares, generada por los cambios de volumen y cuyo modelo se detalla a continuación.…”
Section: Figura 2 Esquema De Control Propuesto La Línea Punteada Reunclassified